2010
DOI: 10.1111/j.1365-2133.2010.09633.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells in the skin lesions and blood of patients with systemic sclerosis and morphoea

Abstract: The quantitative reduction of Tregs, together with that of TGF-beta and IL-10 serum levels, may be responsible for the loss of tolerance observed in both SSc and morphoea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
1
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 43 publications
(36 reference statements)
6
81
1
7
Order By: Relevance
“…We also show a decrease of IL-10-and TGF-b-producing CD4 þ CD25 þ adaptive T cells in SSc patients, as reported in two previous studies that investigated CD4 þ IL-10 þ and CD4 þ TGF-b þ T cells. 20,21 In contrast to our study, Klein et al 26 recently showed no significant difference in the frequency of CD4 þ CD25 high FoxP3 þ from SSc patients as compared with healthy donors. This discrepancy might be due to systemic treatment with corticosteroids and/or cyclophosphamide, which might have restored the frequency of Treg in the studied SSc patients, as described in human lupus erythematous.…”
Section: Controlcontrasting
confidence: 54%
See 1 more Smart Citation
“…We also show a decrease of IL-10-and TGF-b-producing CD4 þ CD25 þ adaptive T cells in SSc patients, as reported in two previous studies that investigated CD4 þ IL-10 þ and CD4 þ TGF-b þ T cells. 20,21 In contrast to our study, Klein et al 26 recently showed no significant difference in the frequency of CD4 þ CD25 high FoxP3 þ from SSc patients as compared with healthy donors. This discrepancy might be due to systemic treatment with corticosteroids and/or cyclophosphamide, which might have restored the frequency of Treg in the studied SSc patients, as described in human lupus erythematous.…”
Section: Controlcontrasting
confidence: 54%
“…In SSc patients, few studies investigated the various Treg subsets and their suppressive function, these also with conflicting results, showing either reduced, 20-22 increased 23,24 or the same [25][26][27] number of circulating Treg cells in peripheral blood as compared with controls. These discrepancies might be mostly due to variations in study techniques, with setting analysis of either CD4 þ CD25 þ , 21,23 CD4 þ CD25 high , 12,25,26 20,24,26 CD25 þ Foxp3 þ CD127 -23 or CD4 þ CD25 high CD127 low subsets. 22 Despite these controversies, in most of these studies of SSc patients' samples, 22,23,26 impaired Treg-suppressive function was associated with SSc disease severity.…”
Section: Introductionmentioning
confidence: 99%
“…E. A. James с соавт. [2010] было показано, что молекулы HLA-DRB1 с общим антигенным эпитопом связывают определен-ные цитруллинированные пептиды, полученные из предполагаемых аутоантигенов, связывая цитруллин, но не аргинин. С другой стороны, к развитию АИЗ может приводить молекуляр-ная мимикрия между аминокислотными после-довательностями SE и вирусными антигенами.…”
Section: P N Kravchenko E K Oleinik Mechanisms Of Immunologicalunclassified
“…Группой авто-ров было показано, что P. gingivalis у больных РА может вызывать неспецифическую активацию лимфоцитов [Bartold et al, 2010;Mikuls et al, 2012]. E. Röhner с соавторами [2010] Примечание. I-A2 (tyrosine phosphatase-like insulinoma Ag 2) -инсулинома-ассоциированный антиген 2; GAD65 (glutamic acid decarboxylase) -глутаматдекарбоксилаза; ОБМ -основной белок миелина; МОГ -ми-глутаматдекарбоксилаза; ОБМ -основной белок миелина; МОГ -ми-; ОБМ -основной белок миелина; МОГ -ми-ОБМ -основной белок миелина; МОГ -ми--основной белок миелина; МОГ -ми-основной белок миелина; МОГ -ми-белок миелина; МОГ -ми-белок миелина; МОГ -ми-миелина; МОГ -ми-миелина; МОГ -ми-; МОГ -ми-МОГ -ми--ми-ми-елин-олигодендроцитарный гликопротеин; CEP-1 (citrullinated-a-enolase peptide) -цитрулированный пептид α-энолаза; H+/K+-ATPase работе показали, что эта бактерия активиру-ет ранние стадии апоптоза хондроцитов, что представляет собой еще один возможный путь разрушения хряща при РА.…”
Section: инфекционная теория развития аиз (молекулярная мимикрия полunclassified
See 1 more Smart Citation